The Influence of Electrode Plate Area in Reducing Turbidity and Color Levels in Peat Water - Akhmadi, Zainal; Chitra, Fara; Wulantika, Daeng (Poltekkes Kemenkes Palu, 2023)
Peat water generally exhibits characteristics ranging from dark brown to black, with high organic content and a pH range between 3.7 and 5.3. These features pose challenges in meeting clean water quality standards, essential for maintaining human health. Consequently, the treatment of peat water becomes a pressing need to enhance its quality for suitable use. Electrocoagulation has emerged as a widely applied method in peat water treatment. This research aims to evaluate the influence of electrode plate area and contact time in reducing turbidity and color in peat water. The research methodology employed a quasi-experimental design known as the One-Group Pretest-Posttest. Thirty test samples were collected with variations in electrode plate areas of 4 x 30 cm, 5 x 30 cm, and 6 x 30 cm. Contact time was varied within the range of 30, 60, 90, 120, and 150 minutes, applying a voltage of 48 volts. The results indicated fluctuations in the increase of turbidity in peat water after the electrocoagulation treatment. A plate area of 6 x 30 cm led to a turbidity increase of 27.33 NTU or approximately 83% after a contact time of 150 minutes. Meanwhile, the color level in peat water decreased by 65 TCU with a 5 x 30 cm electrode plate area after 150 minutes of contact time, achieving an effectiveness of 90% in color reduction. In conclusion, the electrode plate area significantly influences the reduction of turbidity and color in peat water. Although there is no discernible effect of contact time on turbidity levels, prolonged contact time has a significant impact on reducing the color level in peat water.